Synthesis of Silver Nanoparticles Balaccida Leaf Extract and Its Anti-Bacterial Activity of E. Coli - Intania Isnaini (Indonesian Journal of Chemistry and Environment, 2022)
The Covid-19 pandemic has become a major problem for public health around the world. One of the ways to prevent Coronavirus is by maintaining hand hygiene using hand sanitizer. The main ingredient of most antiseptics circulating in Indonesia is alcohol which can cause skin irritation. Alcohol substitutes as antiseptics in hand sanitizers are widely available in nature, one of which is the balakacida plant (Chromolaena odorata). The availability of balakacida plants in Indonesia is very abundant as wild plants are often referred to as nuisance plants (weeds). The phytochemical content of balakacida leaves includes saponins, flavonoids, tannins, and alkaloids that have the potential as antibacterial. Balakacida leaf extract has the potential to be used as a source of active ingredients in antiseptic preparations as an alternative to maintain hand hygiene from various parasitic microorganisms. AgNPs are one of the antibacterial and antifungal agents that are effective in inhibiting and killing microorganisms. The optimal variation of CO-SNPs was found at 3 ml of CO-SNPs with an absorption peak of 409 nm and a particle size of 230.1 nm. CO-SNPs produced the best inhibitory value of 12.26 mm on E.coli bacteria.